Utilizing Mobile-Assisted Language Learning (Duolingo) to Foster Metacognitive Awareness and Self-Directed Learning in Non-English Major Students - La Ode Achmad Suherman; Wa Ode Riniati; Sofyan Sukwara Akfan; Munirah Munirah; Natasya Dian Utami; Fitriani Fitriani (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
Technology-based language learning, particularly Mobile-Assisted Language Learning (MALL), is increasingly utilized to support autonomous learning. However, limited research has explored how Duolingo contributes to metacognitive awareness and learning autonomy among non-English major students in Indonesia. This study aims to analyse the impact of Duolingo on these two variables and to explore the relationship between them. Using a mixed-methods approach with a quasi-experimental design, 56 non-English major students from Universitas Muhammadiyah Buton participated in the study. Quantitative data were analysed using the Wilcoxon Signed Rank Test and Spearman Rank correlation, while qualitative data were examined through thematic analysis. The Wilcoxon test results indicated a significant increase in metacognitive awareness (p < 0.001) and learning autonomy (p < 0.001), with a strong positive correlation between them (r = 0.72, p < 0.001). Interviews revealed that Duolingo’s gamification features, such as streaks and leaderboards, helped students become more aware of their learning strategies and more independent in their learning process. This study demonstrates that Duolingo not only facilitates language learning but also enhances students' autonomy and metacognitive awareness.